Corporate Governance Mechanisms In Improving Company Performance - Dini W Hapsari, Wiwin Aminah, Sugiyanto, (International Journal of Advanced Science and Technology, 2020)
Companies that have company performance can provide maximum prosperity to shareholders when the company's stock price increases. Maximizing company performance means being able to maximize the company's shareholders, and this is one of the goals in a company. This research was conducted to test the mechanism of corporate governance (independent commissioners, institutional ownership, managerial ownership and foreign ownership) in improving company performance. This study uses panel data regression analysis, and the sampling method uses a purposive sampling method with a total of 10 construction companies and the study period during 2015-2018—data analysis techniques using descriptive analysis. The results of the study explained that corporate governance with independent commissioners and institutional ownership did not affect improving company performance while managerial ownership, foreign ownership was able to improve company performance.